EFEKTIVITAS DAN DAMPAK PROGRAM KELOMPOK USAHA BERSAMA (KUBE) TERHADAP PENDAPATAN DAN KESEMPATAN KERJA RUMAH TANGGA MISKIN (RTM) DI DESA SANGEH KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Ni Made Yusmini (Forum Manajemen, 2019)
The problem of poverty is one of the problems that has become the center of attention of the government in any country. The purpose of this study was to determine the effectiveness of the KUBE program in Sangeh Village, Abiansemal District, Badung Regency, in addition to knowing the impact of the program in increasing family income and employment opportunities.The measured effectiveness of the input variables includes: socialization, the accuracy of the type of assistance, the timeliness of providing assistance, the accuracy of the amount of assistance and the accuracy of the target. Furthermore the process variables include social guidance and training, mentoring, follow-up guidance, response to complaints,monitoring and evaluation, while output variables include family income and employment opportunities. The sampling method in this study used a saturated sample.Furthermore, the analysis technique used in this study is to apply descriptive and inferential statistical methods.The results of the analysis show that the KUBE program in Sangeh Village is very effective at 85.83 percent. Based on the t-test, the average difference in income and employment opportunities per KUBE participant showed significant results at 5 percent alpha. From the results of the study,KUBE participants'income and employment opportunities increased after receiving the KUBE program assistance.